Penerapan Metode User Centered Design Pada Aplikasi E-Learning Berbasis Android (Studi Kasus: SMAN 3 Sidoarjo) - Arie Krisnoanto; Adam Hendra Brata; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Education and technology are two interdependence thing for human life in the future. Senior high school 3 Sidoarjo is one of school that have e-learning as educational facilities for students and teachers. Facilities that have been running for several years on the official site of this school is still in the development stage and still not used completely well by the school due to lack of interest for using e-learning from students and teachers. Data from statista.com there are 88.37% smartphone Android users until the end of 2017. By viewing and utilizing the current conditions, students and teachers have been using smartphones in their daily activities as well as maximizing the use of school facilities, e-learning implemented on Android smartphones using User-Centered Design method that refers to the user experience to make e-learning application has a good usability value to be used by students and teachers. In addition, UCD method is iterative which means it can explore any needs of end-user that can change directly. The result of data test from USE questionnaire method are usefulness criteria 91.71%, ease of use criteria 83.37%, ease of learning criteria 94.5%, and satisfaction criteria 82,16%. The average score of usability testing using task scenarios had 96.7% success in student user and 94,6% success on teacher user.